Cumulus cell DNA damage linked to fertilization success in females with an ovulatory dysfunction phenotype - Rodrigues, Bárbara; Sousa, Vanessa; Esteves, Filipa; Vale-Fernandes, Emídio; Costa, Solange; Sousa, Daniela; Brandão, Raquel; Leal, Carla; Pires, Joana; Gaivão, Isabel; Teixeira, João Paulo; Nogueira, António J. A.; et al. (Frontiers in Cell and Developmental Biology, 2024)
Intracytoplasmic sperm injection (ICSI) is a widely used technique in fertility centers. ICSI success depends on both nuclear and cytoplasmic oocyte maturation. Cumulus cells, which surround the oocytes, play a pivotal role in oocyte competence. However, the significance of DNA damage in cumulus cells as a marker of fertilization success remains largely unexplored. This study aims to investigate the relationship between DNA damage in cumulus cells of females undergoing ICSI, and oocyte competence, with a focus on in vitro fertilization (IVF) outcomes. We employed the alkaline comet assay to assess DNA damage levels (%TDNA) in cumulus cells and whole blood from 22 potentially fertile females and 35 infertile females, including 20 with an ovulatory disfunction phenotype. Our results revealed significant differences between the levels of %TDNA in cumulus cells and blood. Females with an ovulatory dysfunction phenotype exhibited higher levels of %TDNA in cumulus cells compared to potentially fertile females. Additionally, within the group of females with ovulatory dysfunction, a significant correlation was observed between %TDNA levels and the number of oocytes with two pronuclei. Our findings suggest that blood does not accurately reflect DNA damage in cumulus cells, which was correlated with the fertilization success in females with ovulatory dysfunction. High levels of %TDNA in cumulus cells were associated with a higher likelihood of successful fertilization. Moreover, our results imply that low levels of %TDNA may be linked to oocytes that fail to complete maturation and, consequently, do not fertilize (oocytes with zero pronuclei). Further research with larger cohorts is necessary to validate these findings and to explore potential applications in female fertility. However, our study provides evidence that DNA damage in cumulus cells may serve as a valuable biomarker for predicting fertilization success and oocyte competence.